BCT515: Design and engineering of bio-composite materials / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2018)
This course introduces students to various design and engineering aspects of bio- composite materials. The topics include basic concepts of bio-composite materials, specific gravity and moisture content, elastic properties and stiffness, plastic behaviour and strength, rheological characteristics, dynamic behaviour, failure, layered bio-composite systems, beam design principles, column design principles, and fasteners and connectors.